Relationship and Mechanism Analysis of Soft-Melt Dropping Properties and Primary-Slag Formation Behaviors of the Mixed Burden in Increasing Lump Ore Ratio - Yun-Fei Li; Zhi-Jun He; Wen-Long Zhan; Wei-Guo Kong; Peng Han; Jun-Hong Zhang; Qing-Hai Pang (Metals, 2020)
At present, cost reduction and environmental protection are the mainstream of blast furnace (BF) development and the high lump ore ratio is an effective means. Therefore, it is significant to explore the relationship and mechanism of burden soft-melt dropping and its primary-slag formation behaviors under increasing lump ore ratio. In this paper, the melt–drop test is carried out on the single ore and mixed burden, and obtained primary-slag properties are subjected to analysis. The experimental results show that the primary-slag of lump ore contains a large amount of FeO and SiO2, so it simply produces many low melting point compounds, which cause terrible soft-melt dropping properties and primary-slag formation behaviors. Notably, mixing with sinter and pellet can effectively improve both the properties. With the increase in lump ore ratio, the CaO in the primary-slag decreases, FeO and SiO2 increase, resulting in the melting temperature of the primary-slag sequentially decreasing and the cohesive zone moves to the low temperature zone. In addition, the maximum pressure difference increases, and the gas permeability deteriorates. Increasing the sinter ratio can overcome the defect of high lump ore ratio that can effectively improve the poor softening performance, melting performance and the position and thickness of the cohesive zone. However, because of the pulverization performance, the maximum pressure difference and gas permeability of the burden become worse.